Identification of COL4A4 variants in Chinese patients with familial hematuria - Gao, Yanan; Yuan, Lamei; Yuan, Jinzhong; Yang, Yan; Wang, Jiangang; Chen, Yong; Zhang, Hao; Ai, Yinze; Deng, Hao (Frontiers in Genetics, 2023)
Benign familial hematuria and Alport syndrome are common causes of familial hematuria among children and young adults, which are attributable to mutations in the collagen type IV alpha chain genes, COL4A3, COL4A4, or COL4A5. The study was conducted to identify the underlying genetic causes in patients with familial hematuria. Two unrelated Han-Chinese pedigrees with familial hematuria were recruited for this study. Whole exome sequencing was combined with in silico analysis to identify potential genetic variants, followed by variant confirmation by Sanger sequencing. Reverse transcription, PCR, and Sanger sequencing were performed to evaluate the effect of the detected splice variant on mRNA splicing. A novel heterozygous splicing c.595-1G>A variant and a known heterozygous c.1715G>C variant in the collagen type IV alpha 4 chain gene (COL4A4) were identified and confirmed in patients of pedigree 1 and pedigree 2, respectively. Complementary DNA analysis indicated this splicing variant could abolish the canonical splice acceptor site and cause a single nucleotide deletion of exon 10, which was predicted to produce a truncated protein. Our study broadened the variant spectrum of the COL4A4 gene and explained the possible pathogenesis, which will benefit clinical management and genetic counseling.